1968
DOI: 10.1002/pol.1968.160060304
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and ionic conductivity in nylon 66

Abstract: SynopsisThe conductivity of dry poly(hexamethy1ene adipamide) (nylon 66) was measured as a function of time and temperature. Three temperature ranges were observed in which the time dependence of conductivity differed: (a) below 8OOC. the conductivity decreased continuously with time; ( b ) between 80°C. and 110'C. the conductivity remained constant over long periods; (c) above 120°C. a continuous decrease in conductivity was again observed. In other experiments the volume of gas evolved from the nylon film wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…In this case, the diffusion constant of deuterium can be estimated from the thickness of the film (about 3 micrometers) and the time constant of deuteration determined by infrared absorption. The relevant equation is 36 n=O (5) where D is the diffusion constant, d is the thickness of the film, and n is a non-negative integer. The diffusion constant of deuterium in the PMG film was estimated to be 9.5 x 10-15 cm 2 s-1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the diffusion constant of deuterium can be estimated from the thickness of the film (about 3 micrometers) and the time constant of deuteration determined by infrared absorption. The relevant equation is 36 n=O (5) where D is the diffusion constant, d is the thickness of the film, and n is a non-negative integer. The diffusion constant of deuterium in the PMG film was estimated to be 9.5 x 10-15 cm 2 s-1 .…”
Section: Discussionmentioning
confidence: 99%
“…Ions supplied from residual impurities have also been considered a source of charge carriers. 9 · 10 PBG 2, CH2C6H 5 In previous papers/ 5 -17 it was shown that the conductivities of poly(y-methyl L-glutamate) (PMG) and nylon 12 were higher in the direction of the chain of hydrogen bonds than in other directions. We therefore consider that the electric conduction of these polymers depends mainly on the nature of hydrogen bonds and is modified by other factors.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Such as Seanor [1,2] has reported that in nylon 6-6, above 120 8C, there is an ionic conduction while below and at least upto 80 8C it is electronic. In PVC, electronic conduction is reported by Flemming and Renicar [3] whereas Kosaki [4] favors hoping ionic mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…For nylon 66 films HZ emission corresponding to the electric field has been observed [3]. A related but more sensitive method, which discriminates the influence of the electric polarity, is used in the present paper to obtain inpulse generotor .…”
Section: Introductionmentioning
confidence: 96%